The Influence of Marketing Strategies and Promotion on Gaining a Competitive Advantage Mediated by Customer Loyalty - Ayu Parlinda Lestari; Retno Purwani Setyaningrum (Journal of Research in Social Science and Humanities, 2025)
This study aims to analyze the influence of marketing strategies and promotion on gaining a competitive advantage with customer loyalty as a mediating variable in the furniture SMEs sector in Kalimalang. The population involved 84 respondents so this research using a quantitative descriptive approach, the research involved 84 respondents selected through a saturated sampling technique. Data were processed using SmartPLS 3.0. The results indicate that marketing strategies have a negative but significant effect on competitive advantage, suggesting the need for careful strategy implementation to ensure alignment with market needs. Promotion shows a positive and significant effect on competitive advantage, emphasizing the role of effective promotional efforts in increasing business competitiveness. While customer loyalty is significantly influenced by both marketing strategies and promotion, it does not significantly mediate the relationship between these two factors and competitive advantage. These findings highlight the importance of strategic marketing alignment and consistent promotional efforts in enhancing competitive positioning, while also underlining that customer loyalty, although important, may not directly strengthen competitive advantage without other supporting factors.